Syndromic paucity of interlobular bile ducts or Alagille syndrome: a case report. - Despontin, K.; Bottu, J.; Decroix, J.; Otte, J.B.; Lachapelle, J.M. (European Journal of Pediatric Dermatology, 2018)
A case of syndromic paucity of interlobular bile ducts (Alagille syndrome) is reported in an 8-year-old child. Chronic intrahepatic cholestasis is described in association with vertebral, cardiovascular, ophthalmogical and renal abnormalities. Various skin manifestations including xanthomas, jaundice and pruritus are present secondary to biliary and liver failure.